Development and clinical validation of a novel photography‐based skin erythema evaluation system: a comparison with the calculated consensus of dermatologists. (6th April 2017) - Cho, M.; Lee, D.‐H.; Doh, E. J.; Kim, Y.; Chung, J. H.; Kim, H. C.; Kim, S.
Abstract: Objective: Erythema is the most common presenting sign in patients with skin diseases, and various methods to treat erythema symptoms have become common. To evaluate changes in erythema, a reliable device that can support objective diagnosis is required. We developed a novel photography‐based system for erythema diagnosis that provides a high‐resolution three‐view photograph taken in a consistent photography environment with a curved surface light source and can be integrated with optimized image processing algorithms. Methods: A new diagnostic algorithm was applied to photographs from 32 patients to determine areas of erythema automatically. To assess the performance in comparison to dermatologists' evaluations, five dermatologists independently evaluate the areas of erythema, and we defined an area called the clinical consensus area of erythema (CCAE), which is based on the majority opinion of dermatologists during evaluation. The CCAE values obtained were compared with the erythema areas determined by the system's diagnostic algorithm. Results: Forty‐one photographs with areas of erythema were evaluated by the proposed system and by dermatologists. The results obtained with the proposed system had a mean accuracy of 93.18% with a standard deviation of 3.52% when compared with the CCAE results. The results also showed that the proposed system could detect erythema areas without any pigmentation. In contrast to assessments by individual dermatologists, use of the CCAE reduced the amount of error that occurred owing to bias or subjectivity. Conclusion: A new erythema evaluation system was developed and validated through CCAE, suggesting that the system can support dermatologists' objective diagnoses of erythema. Abstract : We designed a novel system that acquires high‐quality photographs for quantitatively measuring erythema using a dermatologists' algorithm. The accuracy of the measurement of the erythema area was validated using the clinical consensus area of erythema (CCAE), which consists of the majority opinion of the clinical judgements of five dermatologists and is regarded as a reliable reference.